Assessment of Accuracy in Calculating Hemodynamic Parameters and Left Ventricular Mass According to ECG-Synchronized Myocardial Perfusion Scintigraphic Data: Comparison with Cardiac Multislice Computed Tomography - V. V. Saushkin; K. V. Zavadovskiy (Вестник рентгенологии и радиологии, 2019)
Objective. To assess accuracy in calculating the values of end-diastolic and end-systolic volumes (EDV and ESV), ejection fraction (EF), and left ventricular (LV) mass, which are obtained according to ECG-synchronized myocardial perfusion scintigraphy (ECG-MPS) on a CZT  camera versus those of cardiac multislice computed tomography (MSCT).Material and methods. Thirty-four patients (mean age, 62 ± 5 years) with suspected coronary heart disease or its previously established diagnosis were examined. All the patients underwent MSCT coronary angiography and myocardial perfusion scintigraphy with 99mTc-methyxy-isobutyl-isonitrile. For a comparative analysis, the investigators used the EDV, ESV, FV and LV mass values determined by ECG-MPS at rest and cardiac MSCT. The studies were conducted on a 64-slice SPECT/CT hybrid scanner (Discovery 570c, GE Healthcare, USA).Results. The analysis of the results obtained by both methods revealed statistically significant differences in the values of EDV (MSCT: 168 (145–210) ml; ECG-MPS: 112 (94–141) ml; p < 0.05), ESV (MSCT: 72 (49–83) ml; ECG-MPS: 44 (32–66)  ml; p < 0.05), and LV  mass (MSCT:  123 (107–143)  g; ECG-MPS: 140 (124–168)  g; p < 0.05).  There were no significant differences in LV EF  (MSCT:  64 (54–69)%; ECG-MPS: 61 (50–66)%; p > 0.05).  There was a statistically  significant correlation between the values of EDV,  ESV,  and LV  mass (r = 0.81; r = 0.78; r = 0.82, respectively, p < 0.05) and a mean correlation of LV EF  (r = 0.66; p < 0.05). The Bland–Altman analysis showed that the values of EDV, ESV, and LV mass had statistically significant differences. The consistency limits for the indicators were as follows: EDV, 9–105 ml; ESV, 9–55 ml; LV  mass, 51.6–20.7  g. There was a measurement consistency only for EF  (consent  limits, 16.9–18.4%; p < 0.05). Linear regression equations were calculated, which allow determination  of exact values for the volume indices and LV mass according ECG-MPS data.Conclusion. The scintigraphic method versus MSCT yields significantly smaller volumes (EDV and ESV) and higher LV mass. The  ECG-MPS values for EDV, ESV, EF, and LV mass have a statistically significant strong correlation with MSCT findings. At the same time, a good consistency of measurements was found only for LV EF.